2022
DOI: 10.1002/ctm2.1013
|View full text |Cite
|
Sign up to set email alerts
|

MTHFR inhibits TRC8‐mediated HMOX1 ubiquitination and regulates ferroptosis in ovarian cancer

Abstract: Dear Editor,The study is the first to confirm that methylenetetrahydrofolate reductase (MTHFR) could inhibit HMOX1 ubiquitination degradation by competitive interaction with TRC8, followed by blocking the occurrence of ferroptosis in ovarian cancer (OV) cells, and promote the tumour cells growth. OV attributes to the world's second most familiar cause of gynaecologic cancer death. 1 Recent research studies identified that the polymorphisms of MTHFR correlate with the risk of common gynaecological cancers. 2,3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Ubiquitination modification has long been an area of keen interest for researchers, especially in the field of protein regulation ( Wang et al, 2022 ; Zhang et al, 2023b ). The discovery that ubiquitination targets proteins for proteasomal degradation earned the Nobel Prize in Chemistry in 2004.…”
Section: Discussionmentioning
confidence: 99%
“…Ubiquitination modification has long been an area of keen interest for researchers, especially in the field of protein regulation ( Wang et al, 2022 ; Zhang et al, 2023b ). The discovery that ubiquitination targets proteins for proteasomal degradation earned the Nobel Prize in Chemistry in 2004.…”
Section: Discussionmentioning
confidence: 99%
“…And this study has been approved by the Ethical Committee of Xiangya Hospital, Central South University. The immunohistochemistry (IHC) analysis was conducted as previously described 21,22 . In brief, the IHC Select® HRP/DAB kit (Millipore, # DAB150) was used to conduct the immunohistochemical staining of FHOD1 (1:150) and HSPB1 (1:150).…”
Section: Methodsmentioning
confidence: 99%
“…MTHFR is the rate-limiting enzyme that catalyses the conversion of 5,10-methylenetetrahydrofolate to 5-methyltetrahydrofolate. 76,77 A study showed that increasing the concentration of unmetabolised folic acid could decrease the number and cytotoxicity of NK cells. 78 In addition, the polymorphisms of MTHFR could influence the regulation of immune cells.…”
Section: Methylenetetrahydrofolate Reductasementioning
confidence: 99%